Protective Effect of Fluoride Varnish Containing Trimetaphosphate against Dentin Erosion and Erosion/Abrasion: An in vitro Study - Danelon, Marcelle [UNESP] (2020)
This in vitro study evaluated the protective effect of fluoride varnishes containing sodium trimetaphosphate (TMP) against dentin erosion and abrasion. Specimens of coronal dentin were divided into: Placebo, 2.5% NaF, 5% NaF, 2.5% NaF + 5% TMP, and 5% NaF + 5% TMP groups (n =24/group). After single application of the varnishes, the samples were immersed in citric acid (0.05 mol/L, pH = 3.2, 5 min) followed or not by brushing, and the dentin wear was assessed after 5 days. Varnishes containing fluoride + TMP led to the lowest wear. TMP varnishes showed a superior effect against dentin erosive wear.